Evaluation of cervical and uterine size, at 4 weeks postpartum, as a predictor of subsequent fertility in Jersey cattle - Poock, Scott E. (2020)
Uterine and cervical size of Holstein dairy cows is reported among reasons for a decline in dairy cow fertility. Therefore, the objectives of this study were to (a) determine whether size of the cervix and uterus at 4 weeks postpartum impacted subsequent fertility at first service in Jersey cattle, (b) determine whether progesterone level at 4 weeks postpartum impacted cyclicity and (c) the association of the presence of corpus luteum and uterus and cervix size. Body condition scores at calving, presence of postpartum diseases, parity number and milk weights were taken from lactating Jersey dairy cows (N = 147) for 28 days postpartum. During the fourth week postpartum, a blood sample was obtained for progesterone concentration, and transrectal ultrasonography was performed by a high-resolution ultrasound machine to determine cervical and uterine horn diameter, as well as ovarian structures measurements. Correcting for parity number, BCS at calving, presence of diseases and milk yield, cows with a cervix >2.54 ± 0.63 cm and uterine horn >2.25 ± 0.59 cm were less likely to become pregnant at first service (p = .04 and p = .003, respectively). The cows with larger cervix had a trend to be less likely to have a corpus luteum present at the 4th week of lactation (p = .067). Cows with larger uterine horn size were less likely to have a corpus luteum present at the 4th week of lactation (p = .015). It is concluded that a larger cervix and/or uterus during the postpartum was associated negatively with fertility and cyclicity in Jersey cows.